Analisis Hubungan antara Eco SERVQUAL dan Customer Satisfaction dengan Peran Moderasi Gender, serta Revisit Intention pada Green Hotel di Indonesia - Huda, Arifah Nur; Setyowardhani, Hapsari (Sekolah Tinggi Ilmu Ekonomi Indonesia (STEI) Jakarta, 2023)
Indonesia is well-known as one of the countries with world-famous tourism destinations. Indonesia continues to strive to improve sustainable tourism programs, one of which is through the hotel industry. The hospitality industry supports commitments to reduce carbon emissions, one of which is through the green hotel program. Competition among green hotels in providing service excellence encourages companies to provide the best service quality so that visitors feel satisfied and want to return to stay. This study examines the relationship between Eco Service Quality and Customer Satisfaction with the moderation of gender and the effect of Revisit Intention through the moderation role of gender. Data was collected by distributing questionnaires to 220 respondents. Structural Equation Modelling (SEM) was employed to analyze the data. This study found that Eco Service Quality significantly affects customer satisfaction, ultimately making visitors want to stay again at a future time and opportunity. The role of gender is also proven to have a moderating role in the relationship between Eco Service Quality and customer satisfaction.